Nomination of Regents Election and Head Deputy with A Couple of Candidates for The of 2017 In The District Of Pati - Supriyanto Supriyanto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
The enactment of Act No. 32 2004 is a gateway democratic progress at the local level, which mandates the direct election of regional heads, but as time goes direct elections, emerging phenomenon of elections with one candidate, reflecting the absence of competition in democracy to elect candidates for local leaders. The nomination process that provides an opportunity for citizens to come forward as a potential leader of the path of individual regions or lines of political parties are still unable to stem the phenomenon of the election by one paslon. The weakening of the political party cadres to create a cadre of local leaders, and the difficulties of citizens who want to get ahead of the path of the individual in seeking support to meet the predetermined, a major factor in the increasing phenomenon of the election by one paslon in any implementation of direct election. It also occurs in Pati Regency, Central Java province on Phase Two simultaneous elections in 2017 were only followed by one candidate, that candidate H. Haryanto, SH, MM, M.Si and H. Saiful Arifin. based onit, prompted the authors to examine the management of the Regent and Vice Regent Election of Pati with one candidate in Pati regency.Keywords: Starch 2017 Elections, Elections One Paslon, Direct Election Phenomenon.